Are there specific readers of oxidized 5‐methylcytosine bases?. (2nd August 2016) - Song, Jikui; Pfeifer, Gerd P.
Abstract : 5‐methylcytosine (5mC) was long thought to be the only enzymatically created modified DNA base in mammalian cells. The discovery of 5‐hydroxymethylcytosine, 5‐formylcytosine, and 5‐carboxylcytosine as reaction products of the TET family 5mC oxidases has prompted extensive searches for proteins that specifically bind to these oxidized bases. However, only a few of such "reader" proteins have been identified and verified so far. In this review, we discuss potential biological functions of oxidized 5mC as well as the role the presumed reader proteins may play in interpreting the genomic signals of 5mC oxidation products. Abstract : Oxidation of 5‐methylcytosine (5mC) to 5‐hydroxymethylcytosine, 5‐formylcytosine, and 5‐carboxylcytosine by TET proteins can lead to DNA demethylation. However, the oxidized 5mC bases are rather stable and may function as negative marks for 5mC readers. Intriguingly, proteins that bind to oxidized 5mC have now been identified and characterized by structural studies.